SHIFTING GENDER NORMS AND SEXUALITY QUESTIONS TOWARDS TRANSFORMING WOMANHOOD IN RAVI VARMA’S PAINTINGS - Vinayakaselvi, M. Angkayarkan; Nair. U, Lakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Womanhood is identified as a fluid construct shaped by personal agency, social norms and cultural construction, intersecting the dimensions of identity, gender and sexuality. Exploring its cultural representations and meanings in art forms is crucial to understanding how the visual narratives challenge, reinforce or transform societal perceptions of womanhood over time. The paper analyses the transforming dimensions of womanhood, focusing on representations of gender norms, sexuality, and the female body in the select paintings of Raja Ravi Varma. Varma’s paintings serve as a vital medium for decoding the roles and identities of women, offering insight into the complex interplay between art, culture, and gender dynamics. The paintings act as a prism that resonates with the concept that the construction of womanhood is a fluid and dynamic process subject to change. The study examines how Varma’s artistic expressions hint at the sociocultural transformations of the early twentieth-century Kerala society. The paper employs feminist and visual analysis to explore the changing dimensions of womanhood and its representation in select paintings. It interrogates the strategic confrontations made by the artist on the traditional hegemonic narratives of womanhood construction and the artistic strategies used to reflect the societal transitions shaping womanhood in Kerala during the transformative period. Theoretical insights for visual analysis are derived from Van Leeuwen, Laura Mulvey, and James Rendell. Conceptual frameworks are adapted from the insights of G. Arunima, Niharika Dinkar, Uma Chakravarti and Partha Chatterjee.